THE CHALLENGES AND PECULIARITIES IN THE TRANSLATION OF RELIGIOUS TERMINOLOGY - Abdualimova Lobar G'aybulla qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the challenges and specific features associated with  the  translation  of  religious  texts.  Religious  texts  possess  unique  linguistic, cultural, and contextual characteristics that pose particular difficulties for translators. The study examines the semantic, stylistic, and pragmatic nuances that require careful consideration  during  translation  processes.  The  research  identifies  common  issues faced by translators, such as preserving sacred meanings, interpreting metaphors, and conveying doctrinal concepts accurately. The article also highlights the importance of balancing literal fidelity with interpretative clarity in religious translation.